(untitled) (Journal of Engineering Science, 2021)
Bangladesh Railways (BR) is an integral part of the country’s transportation system since the British era. At present it covers a length of 2,877 route kilometres. Train accident data collected from BR revealed that train accidents reduced from 590 per year for 2001-10, to 250 per year for 2010-2015 and to 166 for 2015-16. Data also shows that derailments are the major concern in railway safety. Mixed railway gauges, rail weight, battered and damaged rails, low sleeper density and damaged sleepers, lack of maintenance of fittings and fastenings, and inadequate amount of ballasts are the main reasons for such derailments. So as a safety approach against derailments BR has taken rail track rehabilitation projects as well as speed restriction programs. 2015-16 data showed benefit of such restriction program. A speed map is prepared according to the speed restriction program and speed capacity of different sections of the railway network. Journal of Engineering Science 12(1), 2021, 57-62